Sams teach yourself JavaServer pages in 21 days - Holzner, Steven (Sams teach yourself in 21 days., 2003)
Sams Teach Yourself JavaServer Pages in 21 Days offers a proven tutorial format to teach JSP in 21 example-driven lessons. This book is for Web publishing professionals migrating to JavaServer Pages for its ability to create dynamic, interactive Web sites and separate presentation from Java code running behind the scenes. The book starts by explaining the relationship between JSP and Java Servlets and the basics of JSP functions and features. You'll then learn how JSP handles data, interacts with Java components, tracks users, and more. Later chapters discuss debugging, working with databases, XSLT and XML, using the Struts framework from Apache, handling binary data like graphics, and deploying JSP applications. Each topic is illustrated with many working examples that the reader can understand and put to work immediately. Throughout the book the author provides pointers to upcoming developments in JSP 2, to ensure that you are prepared for changes in the new version.